Anaesthetic management of patients with myopathies. Issue 10 (October 2017) - Schieren, Mark; Defosse, Jerome; Böhmer, Andreas; Wappler, Frank; Gerbershagen, Mark U.
Abstract : N/A: The anaesthetic management of patients with myopathies is challenging. Considering the low incidence and heterogeneity of these disorders, most anaesthetists are unfamiliar with key symptoms, associated co-morbidities and implications for anaesthesia. The pre-anaesthetic assessment aims at the detection of potentially undiagnosed myopathic patients and, in case of known or suspected muscular disease, on the quantification of disease progression. Ancillary testing (e.g. echocardiography, ECG, lung function testing etc.) is frequently indicated, even at a young patient age. One must differentiate between myopathies associated with malignant hyperthermia (MH) and those that are not, as this has significant impact on preoperative preparation of the anaesthesia workstation and pharmacologic management. Only few myopathies are clearly associated with MH. If a regional anaesthetic technique is not possible, total intravenous anaesthesia is considered the safest approach for most patients with myopathies to avoid anaesthesia-associated rhabdomyolysis. However, the use of propofol in patients with mitochondrial myopathies may be problematic, considering the risk for propofol-infusion syndrome. Succinylcholine is contra-indicated in all patients with myopathies. Following an individual risk/benefit evaluation, the use of volatile anaesthetics in several non-MH-linked myopathies (e.g. myotonic syndromes, mitochondrial myopathies) is considered to be well tolerated. Perioperative monitoring should specifically focus on the cardiopulmonary system, the level of muscular paralysis and core temperature. Given the high risk of respiratory compromise and other postoperative complications, patients need to be closely monitored postoperatively.